Essentials of testing and assessment : a practical guide for counselors, social workers and psychologists - Neukrug, Edward S.; Fawcett, R. Charles (Thomson/Brooks/Cole, 2010)
This undergraduate textbook examines how formal and informal tests are created, scored, and interpreted by mental health professionals when evaluating clients, and surveys the various techniques commonly used for assessing educational ability, intelligence, career and occupational aptitude, and clinical issues